(untitled) (Al-NASR, 2024)
In an increasingly vigorous business world religion and culture are influential factors in business development. Islam is the second largest religion so there is a dire need to present a holistic picture of the Islamic perspective of entrepreneurship. This paper demonstrates the Islamic principles of entrepreneurship and Islamic entrepreneurial ethics by utilizing the Quran, Hadith, and other available literature. The primary goal of this paper is to unravel the approach of Islam as a religion towards business activity and entrepreneurial activity. In addition, this paper focuses on how Islam as a religion affects entrepreneurial activity from micro to macro levels. The major themes of the study are halal, haram, taqwa, utilization of resources, business financing, and social and entrepreneurial responsibilities. In conclusion, the study regards Islam as an entrepreneurial religion. Topics for further recommendation are also given at the end for future researchers.